Building Faculty Learning Communities – Edited by Milton D. Cox and Laurie Richlin - Spyker, Stephen K. (Teaching theology and religion, 2006)
Books reviewed: Building Faculty Learning Communities. Edited by Milton D. Cox and Laurie Richlin. New Directions for Teaching and Learning, No. 97. San Francisco: Jossey-Bass Publishers, 2004. v + 163 pages. ISBN 0-7879-7568-0. USD27.00.